2019
DOI: 10.1002/mc.22994
|View full text |Cite
|
Sign up to set email alerts
|

ETS1 is coexpressed with ZEB2 and mediates ZEB2‐induced epithelial‐mesenchymal transition in human tumors

Abstract: Epithelial‐mesenchymal transition (EMT) is an embryonic program that is reactivated in cancer and regulates the invasion and metastasis of tumor cells. Zinc finger E‐box binding homeobox 2 (ZEB2) induces EMT by upregulating matrix metalloproteinases (MMP), yet MMP genes lack ZEB2 binding motif in their promoters. Recently, expression of MMPs was associated to the activation of ETS1 transcription factor; however, a link between ZEB2 and ETS proto‐oncogene 1, transcription factor (ETS1) remains to be elucidated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 63 publications
0
24
0
Order By: Relevance
“…ETS1 is associated with poor prognosis and therapy resistance in most of the cancers [107][108][109][110]. ETS1 is required for ZEB2-induced EMT phenotype, where it regulates ZEB2-mediated expression of Twist and MMP-9 [111], and can function as a master regulator of TGF-β-associated EMT in the mesenchymal subtypes of head and neck squamous cell carcinoma (HNSCC) [112]. ETS1 has been shown to regulate cellular metabolism in ovarian cancer cells resulting in the up-regulation of key enzymes involved in glycolysis [113].…”
Section: Ets1mentioning
confidence: 99%
“…ETS1 is associated with poor prognosis and therapy resistance in most of the cancers [107][108][109][110]. ETS1 is required for ZEB2-induced EMT phenotype, where it regulates ZEB2-mediated expression of Twist and MMP-9 [111], and can function as a master regulator of TGF-β-associated EMT in the mesenchymal subtypes of head and neck squamous cell carcinoma (HNSCC) [112]. ETS1 has been shown to regulate cellular metabolism in ovarian cancer cells resulting in the up-regulation of key enzymes involved in glycolysis [113].…”
Section: Ets1mentioning
confidence: 99%
“…In hematopietic stem cells, for example, TWIST1 binds to the promoter of Gata2 and induces its transcription (Kulkeaw et al, 2017), while in nasopharyngeal carcinoma cells, GATA2 induces EMT by binding to the promoter of Twist1 and activating its expression (Wang et al, 2017b). Furthermore, ETS1 and ZEB2 activate each other's transcription (Katoh and Katoh, 2009;Yalim-Camci et al, 2019).…”
Section: Key Transcription Factors For Endothelial and Mesenchymal Idmentioning
confidence: 99%
“…We showed that ERN1 knockdown of glioma cells leads to a strong down-regulation of the expression of ZEB2 gene under glucose deprivation. Homeobox protein ZEB2 is functioning as an oncogene in human laryngeal squamous cell carcinoma and acts as an upstream positive regulator of ETS1 (ETS proto-oncogene 1) (Li et al 2019;Yalim-Camci et al 2019). Furthermore, transcription factor ETS1 is coexpressed with ZEB2 and mediates ZEB2-induced epithelial-mesenchymal transition in human tumors (Yalim-Camci et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Homeobox protein ZEB2 is functioning as an oncogene in human laryngeal squamous cell carcinoma and acts as an upstream positive regulator of ETS1 (ETS proto-oncogene 1) (Li et al 2019;Yalim-Camci et al 2019). Furthermore, transcription factor ETS1 is coexpressed with ZEB2 and mediates ZEB2-induced epithelial-mesenchymal transition in human tumors (Yalim-Camci et al 2019). At the same time, transcription factor ZEB2 regulates the activity of ETS1 by directly binding to its promoter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation